The Reactualization of Sipakatau, Sipakalebbi, and Sipakainge’ Values Using La Galigo Comic with Augmented Reality - Tikson, Shinta Dewi Sugiharti; Samintang; Firdaus; Andi Khaerun Nisa; Wahda; Mustafa, Fahrina (International Journal of Elementary Education, 2023)
Base on observation there is no educative and interactive learning media in local content lessons related to strengthening student character. This study aims to analyze student interest and enthusiasm in local content lessons, understand the values, diversity, and inclusivity contained in La Galigo through Augmented Reality (AR)-based comic. This study is use Wilcoxon signed-rank test is used to compare the pre-test and post-test, also comparing anecdotal notes of student activities. A total of 14 students from the 4th and 5th grade participated in this program. Data collection is use observations, anecdotal records, and in-depth interviews were also used to assess students' personalities. Based on the evaluation of the pre-test and post-test, there is an increase in students' knowledge after the comic learning method is used. Changes in student’s knowledge and attitude are accomplished through the use of continuous assessment indicators and the involvement of the teacher in the classroom. It is hoped that this innovation can help students develop better character by incorporating trisipaka-based values (sipakatau, sipakalebbi, and sipakainge') into their daily lives.